Undetectable caeruloplasmin values in a patient with autoimmune chronic active hepatitis. Issue 5 (May 1991) - Ilan, Y; Hillman, M; Oren, R; Galun, E; Shalit, M
Abstract : Caeruloplasmin is an alpha 2 protein produced in the liver that is responsible for transporting copper in the blood. Caeruloplasmin values are usually high in patients with chronic liver diseases, including chronic active hepatitis: low values, however, are characteristic of Wilson's disease. The case of a 17 year old woman with very low caeruloplasmin values and chronic active hepatitis of the lupoid type is described. Steroid treatment resulted in an increase in the caeruloplasmin concentration and clinical improvement.